Mubda al-shuriy fi al-islam wa-nazam al-siasi fi Libya - Nada A'bdul al-Rahman Muhamad A'bututah
The title of the study is the principle of consultation in Islam and the political system in Libya (a comparative study) which comprises of three chapters include several sections. The first chapter touches on the principle of consultation from the theoretical perceptive on the general principle of the basic principles of Islam, where inductive approach was used to analyze different views of many Muslims scientists and scholars and provide different evidences. The second chapter of the study highlights on various political regimens that have passed on Libya by using descriptive analytical approach which gives a wider range of political systems since Libya's independence in 1951, to the current interim system post 2011, and a comparison between the principle of consultation in Islam and the political system in Libya in the third chapter by clarifying the extent of the institution's practice and effective application of the political state in the different systems of government as well as looking at the similarities and differences between them, in this chapter a comparative approach was used. The reason for choosing this title is the urgent need to find a democratic political system that regulates political matters and corrects political deviation, and find a solution to the state of turmoil and revolutions, wars and the struggle for power in Libya. However, the researcher believes that there is no democratic system that ensures freedom and justice and equality like the system chosen by God for the Muslims in the management of all their affairs, namely the principle of consultation. The problem of the study is to know any formula for the rule and any nature of the political system in Libya since it gained independence in 1951 and until the February 17, 2011 revolution and the extent of the principle of Shura in actual practice. The study has reached to many results include the most important that the principle of consultation in Islam is an integrated, social political and economic system to achieve equality, justice and freedom desired by all members of society, and the royal parliamentary system of government is the closest to this system principle, where it was mentioned in the royal constitution in 1951, and the institutions used to apply it through the National Assembly by both houses of Representatives and the Senate, and the Libyan people committed to the application of the Shura in the election of the General National Congress the current interim government through free and fair elections exceeded all expectations as the first experience since many years of political persecution and deprivation of political rights to participate in and express an opinion for a period of forty-two years of Muammar Gaddafi's regime, which was reached that this system is an ideal and fake system remained only in the books because Gaddafi possessed absolute power in his hand which is not limited by the Constitution or the law.